Gastrointestinal pathology : correlative endoscopic and histologic assessment - Lauwers, Gregory Y.; Wallace, Michael B. (Michael Bradley) (New Jersey : Wiley-Blackwell, 2021)
"This book is intended to help with the microscopic evaluation and the formulation of a differential diagnosis when interpreting gastrointestinal (GI) biopsies (including methods of cytologic acquisition) in the context of the clinical and endoscopic presentation. It is also intended to help gastroenterologists optimize the acquision, and initial handling of biopsy specimens to facilitate an informative diagnosis The goal is to provide a companion to the diagnostic pathologists and to teach pathology residents /fellows, as well as gastroenterologists, the importance of correlating clinical impression, endoscopic findings and microscopic interpretation (with an emphasis on inflammatory and infectious lesions, rather than neoplasms). To assure that the presentation of the material matches "real-life" a standardized format is used for each major entity reported: Clinical presentation, endoscopic appearance and expectations by the gastroenterologist; specific methods, locations, and numbers of biopsy samples needed for specific conditions, and specific handling requirements for specific conditions; the pathologic part of the text will be classic with description of significant architectural changes, but with emphasis on "pathognomonic" characteristics and secondary features; differential diagnosis presented sequentially presented on a) clinical presentation; b) microscopic appearance and c) results of ancillary studies (when performed); suggestions for reporting (i.e., key elements to include in the pathology reports) are offered where appropriate; simple clinical management clues based on the pathologic will conclude each section"--
PRINCIPAL of BIOSPYDIAGNOSI -- ESOPHAGUS-Inflammatory Conditions -- ESOPHAGUS-Neopastic Conditions -- STOMACH- Inflammatory Conditions -- STOMACH-Polypoid Lesions -- STOMACH- Neoplastic Conditions -- DUODENUM- Inflammatory Conditions -- SMALL INTESTINE-Inflammatory Conditions -- SMALL INTESTINE- Neoplastic Conditions -- COLON Inflammatory Conditions -- COLON-Polypoid Lesions -- COLON-Neoplastic Conditions -- ANUS Inflammatory Conditions -- ANUS- Neoplastic Conditions.
BIB
Keywords: Gastrointestinal Diseases; Gastrointestinal Tract; Endoscopy, Gastrointestinal; Electronic books